KORELASI ANTARA POLA ASUH ORANG TUA, INTERAKSI PEER GROUP DAN KEAKTIFAN PESERTA DIDIK TERHADAP HASIL BELAJAR MATEMATIKA KELAS VII SMPN 3 ABIANSEMAL - Ni Luh Sintya Dewi (LPPM Universitas Bina Bangsa, 2022)
The Indonesian nation as a developing country will not be able to progress as long as it does not improve the quality of our nation's human resources. The nation's quality of life can increase if it is supported by an established education system. So as to be able to think critically, creatively and productively to create an intelligent society. In general, many students obtain learning outcomes under the minimum completeness criteria caused by several factors, namely internal factors and external factors. Internal factors are factors from within students such as learning motivation, student activity, talents and interests, discipline and responsibility. External factors or external factors such as the environment and instruments also affect learning outcomes. The instruments in question include curriculum, teachers, methods, strategies, infrastructure, learning support and parenting patterns. This research is classified as correlational research because the independent variables in this study are not directly controlled and occur or have existed before. The purposes of this study were (1) to determine the relationship between parenting style and learning outcomes in mathematics, (2) to determine the relationship between peer group interaction and learning outcomes in mathematics, (3) to determine the relationship between student activity and learning outcomes. mathematics, (4) to determine the relationship between parenting style, peer group interaction, student activity towards mathematics learning outcomes. Based on the results of multiple regression analysis, it was obtained that F_count was 449.040 which was greater than F_table, which was 2.733 at a significance level of 5% (α=0.05). This means that F_count > F_table, then H_0 is rejected and H_adi is accepted, which means that there is a jointly significant relationship between parenting parents (X1), peer group interaction (X2) and student activity (X3) on learning outcomes for class VII SMPN 3 Abiansemal